2019
DOI: 10.4103/ijpc.ijpc_26_19
|View full text |Cite
|
Sign up to set email alerts
|

“End-of-life care is more than wound care”: Health-care providers' perceptions of psychological and interpersonal needs of patients with terminal cancer

Abstract: Aim: People diagnosed with cancer and in end-of-life care may have a range of needs. These needs may be inadequately expressed, recognized, or responded to by family members and health-care providers. The present study aimed at exploring health-care providers’ perceptions of the interpersonal needs, psychological needs, and unfinished business among terminally ill cancer patients during the end-of-life care. Methods: The sample consisted of 11 health-care providers, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Para Pinto el at. (2019) 20 , as principais preocupações psicológicas desses pacientes são sobre afirmações de emoções negativas, angústias com à saúde mental e enfrentamento da morte. Os profissionais que dão apoio espiritual a esses pacientes também fazem parte da equipe multidisciplinar.…”
Section: Resultsunclassified
“…Para Pinto el at. (2019) 20 , as principais preocupações psicológicas desses pacientes são sobre afirmações de emoções negativas, angústias com à saúde mental e enfrentamento da morte. Os profissionais que dão apoio espiritual a esses pacientes também fazem parte da equipe multidisciplinar.…”
Section: Resultsunclassified
“…On the contrary, similar studies conducted in Sri Lanka identified major knowledge and attitude deficiencies regarding end-of-life care. It highlighted the need for compulsory undergraduate and postgraduate medical curricula training, with supervised simulations and real-life encounters [ 6 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in the human sciences, the distinction made between pain and suffering is less radical. For example, the concept of “global pain” defined by Clark (1999), Krawczyk et al (2018), and Pinto et al (2019) removes the boundaries between pain and suffering. For these authors, pain is more than a physical matter of sensation since it includes the interrelations between social, physical, psychological, and spiritual dimensions.…”
Section: Introductionmentioning
confidence: 99%